Experimental and numerical investigation of hybrid laser arc welding process and the influence of welding sequence on the manufacture of stiffened flat panels. (January 2021) - Hammad, Ahmed; Churiaque, Cristina; Sánchez-Amaya, José María; Abdel-Nasser, Yehia
Graphical abstract: Highlights: A novel three-dimensional coupled thermo-elastic-plastic FE model is developed. T Hybrid laser arc welding (HLAW) tests are employed to validate the FEM model. FE results provide excellent agreement with the HLAW experimental measurements. A semi-industrial scale model is built to study four different welding sequences. The welding sequence plays an important role in the deformation of the structures. Abstract: Hybrid laser arc welding (HLAW) has gained growing attention from both industry and academic laboratories for its high efficiency and weld quality. The objective of the present paper is to develop a nonlinear finite element method for predicting the weld-induced deflection and residual stress of semi-industrial scale stiffened panel, using a novel heat source model. The novel hybrid heat source consists of a Goldak's double-ellipsoid mathematical model representing the arc source, combined with a truncated cone Gaussian mathematical model to simulate the laser source. For this purpose, three-dimensional coupled thermo-elastic-plastic finite element model has been developed with ABAQUS using an additional numerical subroutine of DFLUX written in the Fortran programming language to simulate the volumetric heat flux distributions of the HLAW process. The finite element method (FEM) is verified by comparison with experimental measurements of T-joint small-scale naval EH36 steel specimens, welded in horizontal position with full penetration using hybrid laser-arc welding process (HLAW). A good agreement is observed between the numerical results and the experimental measurements, confirming that the model developed in the present paper can be used effectively to predict the deformation behaviour of the stiffened plate structures during shipbuilding. The effect of changing welding sequence on the semi-industrial scale stiffened panel has been also studied. It is concluded that the welding sequence plays an important role in the deformation of the structures. A change of direction in the middle section, in combination with alternation of the welding paths between two consecutive reinforcements welding, leads to a significant decrease of distortion.